2018
DOI: 10.1016/s2095-3119(17)61889-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and selection of an artificial diet for the coconut black-headed caterpillar, Opisina arenosella, based on orthogonal array analysis

Abstract: Opisina arenosella has been an outbreak pest of coconut trees in southern China since 2013. To develop efficient control methods for this invasive pest, adequate rearing protocols are desirable. In this study, an orthogonal array of artificial diets with 11 factors at 3 levels was deployed for both 2nd-4th and 5th-6th instar larvae of O. arenosella. Biological parameters including survival time of larvae, development time from larva to pupa, pupation rate, emergence rate, and pupal weight were monitored to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Opisina arenosella (Lepidoptera: Oecophoridae) or commonly called the coconut black-headed caterpillar is a harmful defoliator of coconut in many coconut producing countries including India, Sri Lanka (Kumara, 2015), Bangladesh (APPPC, 1987), Pakistan, Myanmar (EPPO, 2014), China (Baoqian et al, 2016;Jin et al, 2018), Thailand (DOA Thailand, 2017) and Malaysia (Nor Ahya et al, 2018). Being polyphagous by nature, this pest also found infesting other crops such as oil palm, jackfruit, cashew (Shameer et al, 2017), date palm, and numerous types of ornamental palms (Murthy & Jalai, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Opisina arenosella (Lepidoptera: Oecophoridae) or commonly called the coconut black-headed caterpillar is a harmful defoliator of coconut in many coconut producing countries including India, Sri Lanka (Kumara, 2015), Bangladesh (APPPC, 1987), Pakistan, Myanmar (EPPO, 2014), China (Baoqian et al, 2016;Jin et al, 2018), Thailand (DOA Thailand, 2017) and Malaysia (Nor Ahya et al, 2018). Being polyphagous by nature, this pest also found infesting other crops such as oil palm, jackfruit, cashew (Shameer et al, 2017), date palm, and numerous types of ornamental palms (Murthy & Jalai, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is important because if a diet is too wet or sticky, larvae can become entangled in the media causing high mortality (Moore & Navon 1974;Rabab et al 2016). A viscous or sticky texture can be caused by an unsuitable or low concentration of a gelling agent, or a formulation with high moisture content, or oily ingredients, as reported by Jin et al (2018). These authors designed an artificial diet for the coconut black-headed caterpillar, Opisina arenosella, and concluded that linseed oil made the diet viscous and sticky, causing mortality of small, early instar, larvae.…”
Section: Resultsmentioning
confidence: 98%
“…A derivative algorithm was used to nd the optimum values in the experimental intervals pre-selected for each input variable (Lan et al, 1994b;Sharma et al, 2006). It was valued to note that some authors have previously announced some viable orthogonal array design applications in biological research (Guo et al, 2022;Jin et al, 2018;Lan et al, 1995;Silveira et al, 1991;Tan et al, 2007;Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%